Vinculum : Poems - Friman, Alice (Book collections on Project MUSE., 2011)
Alice FrimanAEs latest collection, Vinculum, roots for deep connections between people, nature, retrospection, and the inevitable biological destiny of the body. Her poems embrace the painful uncertainty of existence and relationships with clear-cut precision. The defiance and directness in latest work is matched by its musicality, creating a rich but fragile weave of human attachment. Friman is the poet-in-residence at Georgia State University and professor emerita of English and creative writing at the University of Indianapolis.